A sacrificial material approach for spark plasma sintering of complex shapes. (November 2016) - Manière, Charles; Durand, Lise; Weibel, Alicia; Chevallier, Geoffroy; Estournès, Claude
Abstract: An optimized process for the densification of a complex shape part is studied. Production of samples with a complex shape is very difficult in uniaxial die compaction processes because of the thickness differences responsible for densification inhomogeneities. To solve this problem in the case of a particular shape, we propose a solution consisting of homogenization of the shrinkage distances by means of the use of a sacrificial material. This solution was first studied by a finite element approach and then tested experimentally. We obtained a part of complex shape with an overall relative density of 99% and a homogeneous microstructure. Graphical abstract: